Parental Psychological Control and Self-Efficacy as Predictors of Romantic Relationship Power Dynamics - Whittington, D. Drew (Journal of interpersonal violence, 2023)
In the current study, we utilized a person-centered approach to examine the relations of parental psychological control (PPC) and relationship self-efficacy (RSE) to power dynamics in emerging adults’ romantic relationships. College student emerging adults (N = 312) completed measures assessing retrospective PPC, RSE, and perceived self and partner power in current relationships. Latent profile analysis uncovered four relationship types based on reported self- and partner-power: balanced-unified, balanced-interchanging, unbalanced–high self, and unbalanced-high partner. Increases in PPC were related to increased odds of being in an unbalanced relationship. Higher levels of RSE were associated with decreased odds of being in an unbalanced relationship. Further, even individuals in the balanced profile who reported average levels of both self and partner power (balanced-interchanging) reported higher levels of PPC and lower levels of RSE compared to those in the balanced group where levels of both self and partner power were low (balanced-unified). These findings suggest using a person-centered approach to relationship power may advance our conceptualization of power distribution in romantic relationships. Further, experienced family dynamics and one’s sense of self may be especially important for young adults’ tendency to form healthy relationships. The current findings encourage future investigation into the mechanisms by which parental factors predict both dominance and submissiveness in romantic relationships. Understanding predictors of power dynamics may contribute to intimate partner violence prevention and intervention.